2021
DOI: 10.3389/fpubh.2021.730647
|View full text |Cite
|
Sign up to set email alerts
|

Telehealth to the Rescue During COVID-19: A Convergent Mixed Methods Study Investigating Patients' Perception

Abstract: Background: The onset of the pandemic necessitated abrupt transition to telehealth consultations. Although there is a few tools that gauge the patients' perception about their experiences, none of them are contextualized to an emergency in the Middle East and North Africa region. Accordingly, this study aims at developing and validating a tool to address this gap, and deploying it to assess the patients' perception of telehealth services during COVID-19 in Dubai, United Arab Emirates (UAE).Methods: A convergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…In the studies that included qualitative findings, we get an in-depth understanding of the experiences of patients and caregivers with virtual care delivery during COVID-19. For instance, in the study by Al-Sharif et al[ 58 ], they found convenience and safety to be two major advantages to virtual care delivery, especially with the high risk of getting infected with COVID-19. Juarez-Reyes et al[ 59 ] found patient participants expressed gratitude for continued mental health support, and being able to still be a part of virtual group sessions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the studies that included qualitative findings, we get an in-depth understanding of the experiences of patients and caregivers with virtual care delivery during COVID-19. For instance, in the study by Al-Sharif et al[ 58 ], they found convenience and safety to be two major advantages to virtual care delivery, especially with the high risk of getting infected with COVID-19. Juarez-Reyes et al[ 59 ] found patient participants expressed gratitude for continued mental health support, and being able to still be a part of virtual group sessions.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies that used PREMs and also qualitative interviews reported challenges patients and caregivers faced with virtual care, such as feeling rushed during the virtual appointment (2% of PREMs articles) [ 26 , 38 , 48 ], lack of physical contact with the healthcare provider for physical examinations (15% of PREMs articles) [ 21 , 23 , 26 , 35 , 58 , 87 , 88 ], technical challenges (2% of PREMs articles) [ 26 , 29 , 35 , 37 , 43 , 48 , 56 , 77 ], a preference for in-person care delivery (8.5% of PREMs articles) (e.g. due to the lack of personal connection with healthcare provider online) [ 21 , 23 , 28 , 38 , 41 , 54 , 88 , 89 ], and difficulty with communicating symptoms or asking all of their questions (6% of PREMs articles) [ 29 , 87 , 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness of telediabetes modality has been proven through multiple studies. In a pre-COVID meta-analysis of 13 randomized controlled trials, telemedicine was associated with a statistically significant and clinically relevant reduction in HbA1c level but did not show such an effect on blood pressure and LDL cholesterol reduction [ 18 ]. In a systematic review of 37 studies to assess physician satisfaction with telemedicine, which included varied types of telemedicine or provider teleconsultation and different diagnoses or care situations, it was shown that physicians across specialties, geographic locations, practice locations, and care situations appear satisfied with telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“…Most participants (70.0%) believed telemedicine might lower transportation expenses and save time, labour, and costs. In Dubai, Al-Sharif et al [ 16 ] reported high satisfaction levels with telemedicine but identified specific areas for improvement. They found that patients with higher education and those who experienced a shorter duration of teleconsultations were more satisfied, so it is recommended that guidelines define the optimal telemedicine consultation duration.…”
Section: Discussionmentioning
confidence: 99%